Pengaruh Gaya Kepemimpinan, Motivasi Kerja, Lingkungan Kerja, Budaya Organisasi, Dan Disiplin Kerja Terhadap Kinerja Guru Smp Negeri Di Kecamatan Bumiayu - Moh. Algi Faris; Sutarmin Sutarmin (CV. ITTC INDONESIA, 2025)
Human Resource Management is a very important thing in an agency or company. By having good and reliable human resources, the agency will be greatly helped in achieving success and well-executed goals and vision and mission which are influenced by teacher performance. This research aims to analyze the influence of leadership style, work motivation, work environment, organizational culture, and work discipline on the performance of State Middle School teachers in Bumiayu District. The data used in this research is primary data obtained by distributing questionnaires directly. The sample in this study was 109 respondents. The sampling technique uses probability sampling with a simple random sampling method. Data analysis uses multiple linear regression analysis with the help of SPSS v. 26. Based on research results, it shows that leadership style, work motivation, work environment, organizational culture and work discipline have a positive effect on the performance of State Middle School teachers in Bumiayu District